2018
DOI: 10.7326/m17-2740
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Disorders of Pregnancy and Maternal Cardiovascular Disease Risk Factor Development

Abstract: National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(164 citation statements)
references
References 47 publications
8
155
0
1
Order By: Relevance
“…Thus, we cannot rule out that Sister Study participants may differ in terms of preeclampsia risk (and, possibly, risk factors) from the general population. However, as previously noted, the prevalence of preeclampsia in this study is similar to that in another cohort that was not selected based on breast cancer risk …”
Section: Commentsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, we cannot rule out that Sister Study participants may differ in terms of preeclampsia risk (and, possibly, risk factors) from the general population. However, as previously noted, the prevalence of preeclampsia in this study is similar to that in another cohort that was not selected based on breast cancer risk …”
Section: Commentsupporting
confidence: 87%
“…The main limitation of this study is that all information was self‐reported. However, the overall prevalence of preeclampsia in this study (6.2%) was very close to the 6.3% reported for primiparous participants in the Nurses’ Health Study who had given birth between 1964 and 2008 . In our study, 83% of the births occurred in this same period, and 17% between 1947 and 1963.…”
Section: Commentsupporting
confidence: 79%
See 1 more Smart Citation
“…It was shown that women with a history of pregnancy-induced hypertensive disorder had a higher risk of HT than in women with no history of pregnancyinduced HT or PE. An analysis of the Nurses' Health Study II showed that women with a history of pregnancy-induced HT or PE have a higher risk of HT The risk was the highest in the first 5 years after delivery [218]. It should be emphasized that the association between PE and pregnancy-induced HT and subsequent HT can be seen as early as in the first months following delivery.…”
Section: The Risk Of Hypertension In Women With a History Of Gestatiomentioning
confidence: 99%
“…H ypertensive disorders of pregnancy (HDP) complicate 10% to 15% of all pregnancies and are a major cause of maternal morbidity and mortality worldwide, both surrounding pregnancy and across the life course. [1][2][3][4] The American Heart Association recognizes history of HDP as an established risk factor for cardiovascular disease (CVD) in women. 5 Compared with women with a history of normotension in pregnancy, women with a history of HDP have approximately twice the risk of CVD, more than twice the risk of chronic hypertension, a 70% higher risk of type 2 diabetes, and a 30% higher risk of hypercholesterolemia.…”
mentioning
confidence: 99%